Testing of The Insulation Resistance and Turns Test Ratio (TTR) of The Distribution Transformers at PT. XYZ: Pengujian Tahanan Isolasi dan Tes Rasio Tegangan (TTR) Trafo Distribusi di PT. XYZ - Shofiyuddin, Muhammad; Wisaksono, Arief (Procedia of Engineering and Life Science, 2024)
Electricity plays a vital role in human life and the economic growth of Indonesia. Therefore, a reliable electrical transmission and distribution system is essential. Transformers, especially in an industrial context, play a key role in power supply. Transformer maintenance is a critical step in maintaining a stable flow of electricity. This study adopts the Research and Development (R&D) method and focuses on measuring insulation resistance and voltage ratios in the context of transformer maintenance. The research was conducted at the Pole Transformer Substation (GTT) in P. Melati, Sidoarjo Regency, East Java, starting in August 2023. The research variables involve measuring the insulation resistance referring to IEC standards and measuring the voltage ratio to ensure proper transformer performance. The test results indicate that the insulation resistance in the transformer, both on the primary and secondary sides, meets the standards, demonstrating that the transformer functions well and safely. Voltage ratio measurements closely approximate theoretical calculations and fall within a tolerance of ± 0.5%. This study underscores the importance of transformer maintenance in maintaining a stable flow of electricity. Proper maintenance will prevent disruptions that can be detrimental, such as current leakage or short circuits. With good maintenance, the continuity of a reliable and safe electricity distribution service for consumers can be ensured. Highlights : Reliable electrical transmission is crucial for Indonesia's economic growth. R&D method used to measure insulation resistance and voltage ratios in transformer maintenance. Test results confirm proper transformer function and emphasize the importance of maintenance for stable electricity supply. Keywords : Distribution Transformers; electrical energy, transformer, maintenance, insulation resistance, voltage ratio, Pole Transformer Substation.